Reprinting of Kaba and Tambo Books by Kristal Multimedia Publisher - Nur Ahmad Salman Herbowo; Sulastri Sulastri (Wanastra: Jurnal Bahasa dan Sastra, 2020)
This research uses Multimedia Crystal Publisher as a material object. The formal object is using the theory of literary sociology proposed by Robert Escarpit. The study of Escarpit's literary sociology is to analyze matters relating to the production, distribution and consumption of literary books. This study only at the stage of the production process (the process of re-publishing the Kaba and Tambo books). The existence of publishers has an important role in the preservation of folk literature in Minangkabau. Minangkabau folk literature presented with oral traditions is a consideration of the importance of printing the work into books. Minangkabau folk literature is a form of local wisdom in which there are values and philosophies of life from past historical and cultural events. So the current generation needs to know the stories contained in Kaba and Tambo. Publisher's work in reprinting classical literature is a form of efforts to save Minangkabau literature from extinction. Publisher Kristal Multimedia has republished two Tambo books and eighteen Kaba books, the results of which are printed and digital books (e-books). The work carried out by Crystal Multimedia publisher is a form of efforts to preserve literary works based on local wisdom.